PERAN GURU BIMBINGAN DAN KONSELING DALAM MEMBANTU PENCAPAIAN TUGAS PERKEMBANGAN SOSIAL PESERTA DIDIK BERKEBUTUHAN KHUSUS PADA PENDIDIKAN INKLUSI (Studi di SMK Negeri 4 Padang) - Rahayu, Cici Fitri (Bimbingan dan Konseling, 2014)
This research was caused by existence of students of exceptional needs who haveproblem in having socialization. Focus and purpose of this research are how the role of conselor inhelping the achievement of development function of students who have exceptional needs inhaving socialization at school environment with peer friend and having socialization appropriatewith genderâs role. This research was done by using qualitative research with descriptive. Theinformant of this research was counselor, uncommon counselor, studentsâ vice of headmaster andthe students with exceptional needs. The instrumentation that is used in this research was interviewand study of documentation. The researcher used reduction data, presenting data and makingconclusion as the technique of processing data. The result of this research showed that the roles ofcounselor in helping the achievement of development function of students who have exceptionalneeds in having socialization at school environment with peer friend were giving service aboutsocial skill, grouping the students in self development activity which is appropriate with theirspecialty, guiding the students to understand the concept life of democratic. The roles of counselorin helping the achievement of development function of students who have exceptional needs inhaving socialization appropriate with genderâs role were giving service about genderâs role, doingthe activity which support guidance and counselling like appearance of literature, inviting thestudents to observe social life that involve social role between man and woman in society.